Synergistic effects during pyrolysis of binary mixtures of biomass components using microwave-assisted heating coupled with iron base tip-metal. (February 2023) - Li, Longzhi; Cai, Dongqiang; Zhang, Lianjie; Zhang, Yue; Zhao, Zhiyang; Zhang, Zhonglei; Sun, Jifu; Tan, Yongdong; Zou, Guifu
Abstract: The interaction between microwave and tip-metal can cause microwave discharge under appropriate conditions, showing promotion effect on pyrolysis of actual biomass. However, the fundamental studies of biomass component pyrolysis in terms of this method is lack, leading to synergistic effect during pyrolysis of binary mixtures of biomass components unclear. Therefore, the work studied pyrolysis characteristics of individual component (cellulose, lignin, and xylan) and binary mixtures of these components using microwave-assisted heating coupled with iron base tip-metal, and focused on the synergistic effect during the pyrolysis of binary mixtures. It was found microwave-assisted heating coupled with tip-metal had a triggering effect on the pyrolysis of lignin and xylan, reducing initial pyrolysis temperature by half. The maximum pyrolysis rate of the binary mixtures (cellulose-lignin and lignin-xylan) improved with the increase of lignin. The initial pyrolysis of binary mixture comprised by cellulose and xylan was also promoted. Synergistic effect of binary component pyrolysis was strengthened with this method. The pyrolysis synergistic effect of cellulose and lignin was centralized before 350 °C, and the synergistic effect obtained with the binary mixture of lignin and xylan was benefited most from this method. The work provides valuable information on biomass pyrolysis using this method. Graphical abstract: Image 1